2018
DOI: 10.1038/s41598-018-19171-x
|View full text |Cite
|
Sign up to set email alerts
|

Significantly High Modulation Efficiency of Compact Graphene Modulator Based on Silicon Waveguide

Abstract: We theoretically and experimentally demonstrate a significantly large modulation efficiency of a compact graphene modulator based on a silicon waveguide using the electro refractive effect of graphene. The modulation modes of electro-absorption and electro-refractive can be switched with different applied voltages. A high extinction ratio of 25 dB is achieved in the electro-absorption modulation mode with a driving voltage range of 0 V to 1 V. For electro-refractive modulation, the driving voltage ranges from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 32 publications
1
42
0
Order By: Relevance
“…Moreover, they have large interaction lengths due to their weak electro-refractivity. Thus, these devices have large footprints making it challenging to attain the ultra-compact designs using these devices [13][14][15] .…”
Section: Integrated Non-volatile Plasmonic Switches Based On Phase-change-materials and Their Application To Plasmonic Logic Circuitsmentioning
confidence: 99%
“…Moreover, they have large interaction lengths due to their weak electro-refractivity. Thus, these devices have large footprints making it challenging to attain the ultra-compact designs using these devices [13][14][15] .…”
Section: Integrated Non-volatile Plasmonic Switches Based On Phase-change-materials and Their Application To Plasmonic Logic Circuitsmentioning
confidence: 99%
“…Giambra et al [41] demonstrated a broadband electro-absorption modulator with 29 GHz bandwidth by integrating the dual-layer graphene capacitor on the passive SOI waveguide. Besides the dual-layer graphene capacitor, Shu et al [42], Hu et al [43], and Sorianello et al [44] demonstrated the graphene-oxide-silicon capacitor-based waveguide-integrated modulators, in which the gate voltage is applied through the intentionally doped silicon waveguide. Apart from passive straight waveguide structures, the hybrid plasmonic waveguide-integrated modulators were demonstrated with potential for achieving high modulation depth.…”
Section: Waveguide-integrated Graphene Photonic Devices For Communicamentioning
confidence: 99%
“…In addition, resonance wavelength shifts of ring modulators are usually limited to the order of 0.1 nm [4]. Graphene, due to its extraordinary optical and electronic properties, has been extensively studied in optoelectronics, and different kinds of optoelectronic devices have benefited from graphene to achieve better performance, such as modulators [9][10][11], photodetectors [12,13], polarisers [14,15] and so forth. The performance gain can also be extended to ring modulators.…”
Section: Introductionmentioning
confidence: 99%